Employment, wages, and the gender gap in Mexico: Evidence of three decades of the urban labor market - Cecilia Y. Cuellar; Jorge O. Moreno (Latin American Journal of Central Banking (LAJCB), 2022)
This paper analyzes the historical evidence of the gender gap in employment and wages in Mexico. We construct consistent time series from 1988:Q1 to 2019:Q4 using employment surveys, and estimate a model of labor participation in the formal market and wages for each gender and quarter, correcting selection biases. Based on these results, we implement a Blinder-Oaxaca (1973) and Mulligan-Rubinstein (2008) decomposition to estimate the gender gap in wages. Our results suggest the returns to schooling for both genders have decreased in the last two decades, showing a gap of almost 2% in favor of women. The gender wage gap fluctuates around 29.6% once self-selection bias is corrected. The prevalence of differences in expected wages between genders exists due to the "selection bias" and "residual" effects. This work's main limitation is that it focuses only on formal urban employment in 16 metropolitan areas; however, this approach makes it possible to identify long-term trends and structural changes in this market, expanding the evidence of the gender gap in the Mexican economic history.
Keywords: J21; J31; J71; J82; 330; Gender gap; Labor supply; Mexico; Returns to education; Wages